Modeling and simulation of the dynamic behavior of the macaw palm fruit-rachilla system. (April 2022) - Pereira, Mariana Ribeiro; Santos, Fábio Lúcio; Velloso, Nara Silveira; Villar, Flora Maria de Melo; Rodrigues, Mateus Resende
The macaw palm ( Acrocomia aculeata ) is a palm tree native to tropical forests that stand out due to its great potential for oil production. This study was developed with the objective of constructing a high-fidelity model of the macaw palm fruit-rachilla system for the purpose of simulating its dynamic behavior when subjected to mechanical vibrations. The finite element method was used to determine the natural frequencies and modes of vibration of the system. The three-dimensional models of the fruit-rachilla systems were elaborated using CAD3D Fusion 360 software. The modal properties of the fruit-rachilla systems were obtained based on the models developed by varying the elasticity modulus values of the system. The parameters of greatest influence in the estimation of natural frequencies are the elasticity modulus, especially that of the fruit-rachilla joint, and the specific mass. The models that take into account the three-dimensional strains along the rachilla are the least sensitive to variations in the mechanical properties (elasticity modulus and specific mass) and are shown to be more representative of the actual physical system.